Clinical Decision-Making Tool for Safe and Effective Prescription of Exercise in Acute Exacerbations of Chronic Obstructive Pulmonary Disease: Results From an Interdisciplinary Delphi Survey and Focus Groups - Camp, Pat G. (Phys Ther, 2015)
BACKGROUND: Exercise is recommended for people with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD), yet there is little information to guide safe and effective mobilization and exercise for these patients. OBJECTIVES: The purpose of this study was to develop a clinical decision-making tool to guide health care professionals in the assessment, prescription, monitoring, and progression of mobilization and therapeutic exercise for patients with AECOPD. DESIGN AND METHODS: A 3-round interdisciplinary Delphi panel identified and selected items based on a preselected consensus of 80%. These items were summarized in a paper-based tool titled Mobilization in Acute Exacerbations of Chronic Obstructive Pulmonary Disease (AECOPD-Mob). Focus groups and questionnaires were subsequently used to conduct a sensibility evaluation of the tool. RESULTS: Nine researchers, 13 clinicians, and 7 individuals with COPD identified and approved 110 parameters for safe and effective exercise in AECOPD. These parameters were grouped into 5 categories: (1) “What to Assess Prior to Mobilization,” (2) “When to Consider Not Mobilizing or to Discontinue Mobilization,” (3) “What to Monitor During Mobilization for Patient Safety,” (4) “How to Progress Mobilization to Enhance Effectiveness,” and (5) “What to Confirm Prior to Discharge.” The tool was evaluated in 4 focus groups of 18 health care professionals, 90% of whom reported the tool was easy to use, was concise, and would guide a health care professional who is new to the acute care setting and working with patients with AECOPD. LIMITATIONS: The tool was developed based on published evidence and expert opinion, so the applicability of the items to patients in all settings cannot be guaranteed. The Delphi panel consisted of health care professionals from Canada, so items may not be generalizable to other jurisdictions. CONCLUSIONS: The AECOPD-Mob provides practical and concise information on safe and effective exercise for the AECOPD population for use by the new graduate or novice acute care practitioner.